Functional Nanohybrid Materials from Photosynthetic Reaction Center Proteins - Kata Hajdu; Tibor Szabó; Abd Elaziz Sarrai; László Rinyu; László Nagy (International Journal of Photoenergy)
Application of technical developments in biology and vice versa or biological samples in technology led to the development of new types of functional, so-called “biohybrid” materials. These types of materials can be created at any level of the biological organization from molecules through tissues and organs to the individuals. Macromolecules and/or molecular complexes, membranes in biology, are inherently good representatives of nanosystems since they fall in the range usually called “nano.” Nanohybrid materials provide the possibility to create functional bionanohybrid complexes which also led to new discipline called “nanobionics” in the literature and are considered as materials for the future. In this publication, the special characteristics of photosynthetic reaction center proteins, which are “nature’s solar batteries,” will be discussed in terms of their possible applications for creating functional molecular biohybrid materials.